Changes in Distribution of Lower Limb Alignment After Total Hip Arthroplasty for Crowe IV Developmental Dysplasia of the Hip - Sun J; Guo L; Ni M; Shen J; Du Y; Zhang B; Zhang G; Zhou Y (Dove Medical Press, 2021)
Jingyang Sun,1,2,* Lingfei Guo,1,2,* Ming Ni,1 Junmin Shen,1 Yinqiao Du,1 Bohan Zhang,1,2 Guoqiang Zhang,1,2 Yonggang Zhou1,2 1Department of Orthopedics, Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China; 2Medical School of Chinese People’s Liberation Army, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yonggang Zhou; Guoqiang ZhangDepartment of Orthopedics, Chinese People’s Liberation Army General Hospital, Fuxing Road, Haidian District, Beijing, People’s Republic of ChinaTel +8613801287599; +8613601210743Email ygzhou301@163.com; gqz301@126.comPurpose: The purpose of this study was to evaluate the distribution of lower limb alignment in Crowe IV developmental dysplasia of the hip (DDH) before and after total hip arthroplasty (THA).Patients and Methods: We retrospectively included 64 Crowe IV DDH patients (87 hips) who underwent THA between February 2010 and May 2019. Radiographic parameters were measured on full limb length standing anteroposterior radiographs, including hip-knee-ankle angle (HKA), mechanical lateral distal femoral angle (mLDFA), mechanical medial proximal tibial angle (mMPTA), anatomical lateral distal femoral angle (aLDFA), and anatomical tibiofemoral angle (aTFA).Results: HKA improved from 176.54°± 3.52° preoperatively to 179.45°± 4.31° at the last followup (P< 0.001). According to the preoperative HKA, 40 hips were defined as knee valgus alignment. The majority of them were characteristic of a valgus mLDFA and a valgus or neutral mMPTA (35%, 47.5%). After THA, there were still 22 hips defined as knee valgus alignment. More than 50% of them were characteristic of a valgus mLDFA and a neutral mMPTA. Five hips (22.7%) revealed valgus alignment in both mLDFA and mMPTA. Twenty-one hips (24.1%) remained knee valgus alignment before and after surgery. One hip, defined as neutral alignment, preoperatively turned into valgus alignment after surgery.Conclusion: Both preoperative and postoperative sources of valgus alignment were mainly from the femoral side among Crowe IV DDH patients. THA mainly played a positive role in the reconstruction of lower limb alignment in these patients.Keywords: total hip arthroplasty, Crowe IV, developmental dysplasia of the hip, knee alignment